АКТУАЛЬНЕ ПИТАННЯ ЩОДО ПРИНЦИПУ РОЗПОДІЛУ ВЛАДИ: ТЕОРЕТИЧНИЙ АСПЕКТ - Новікова, Євгенія (SUPREMANCE OF LAW, 2018)
The article explores the issue in the theoretical aspect concerning the principle of separation of powers. The author focuses precisely on the distribution of power based on a system of checks and balances, that is, the creation of conditions under which each branch of government functions to achieve common national goals, maintains balance in a common system.
Keywords: democratic state; power; democracy; rights; freedom; people; rule of law; authoritarian form of government